"Trunk‐like" heavy ion structures observed by the Van Allen Probes. Issue 10 (27th October 2015) - Zhang, J.‐C.; Kistler, L. M.; Spence, H. E.; Wolf, R. A.; Reeves, G.; Skoug, R.; Funsten, H.; Larsen, B. A.; Niehof, J. T.; MacDonald, E. A.; Friedel, R.; Ferradas, C. P.; et al.
Abstract: Dynamic ion spectral features in the inner magnetosphere are the observational signatures of ion acceleration, transport, and loss in the global magnetosphere. We report "trunk‐like" ion structures observed by the Van Allen Probes on 2 November 2012. This new type of ion structure looks like an elephant's trunk on an energy‐time spectrogram, with the energy of the peak flux decreasing Earthward. The trunks are present in He + and O + ions but not in H + . During the event, ion energies in the He + trunk, located at L = 3.6–2.6, magnetic local time (MLT) = 9.1–10.5, and magnetic latitude (MLAT) = −2.4–0.09°, vary monotonically from 3.5 to 0.04 keV. The values at the two end points of the O + trunk are energy = 4.5–0.7 keV, L = 3.6–2.5, MLT = 9.1–10.7, and MLAT = −2.4–0.4° . Results from backward ion drift path tracings indicate that the trunks are likely due to (1) a gap in the nightside ion source or (2) greatly enhanced impulsive electric fields associated with elevated geomagnetic activity. Different ion loss lifetimes cause the trunks to differ among ion species. Key Points: A new type of ion spectral structure—"trunk‐like"—is reported The trunk structures are present in He + and O + ions but not in H + Simulations are performed to gain insight into the trunk formation mechanism